Willingness of Middle Eastern public to receive COVID-19 vaccines - Abu-Farha, Rana (Saudi Pharm J, 2021)
BACKGROUND: COVID-19 is a pacing pandemic that affected health systems, economy, and social life in the whole world. Currently, there is no treatment for it, but the world is in a race that yielded, in a relatively short time than usual, several approved, promising vaccines in the middle of a storm of debates because of the speed of their production and approval. OBJECTIVE: This study assessed the willingness of Middle Eastern Arab publics to receive COVID-19 vaccines and investigated the factors behind any reluctance to receive them. METHODS: A self-administered questionnaire was distributed through social media applications in four Arab countries (Jordan, Saudi Arabia, Lebanon, and Iraq). Participants’ demographics, medical history, their experience with COVID-19, and their willingness to receive the available vaccines were obtained and analyzed. RESULTS: A total of 2,925 completed forms were included. Only 25% of the participants were willing to receive a vaccine while 33% were hesitant. Iraqis were the most willing to receive it while Jordanians were the least (35% and 17% of each country, respectively). Interestingly, 60% of the acceptors were ready to pay for the vaccine if not covered by governments. It was also found that American vaccines were preffered by 50% of the acceptors. However, 30% of acceptors were unsure of which vaccine is the best and 11% stated that any vaccine is good. Social media were the major source of information about COVID-19 and its vaccines. Finally, predictors of acceptance of the vaccines included living in Saudi Arabia and Iraq, being unmarried, having monthly income > $1,000, holding a medical degree, having high fear from COVID-19, feeling of being at risk of getting infected with COVID-19, and previous reception of influenza vaccine, whereas predictors of refusal included female sex and previous infection with COVID-19. CONCLUSION: Middle Eastern Arabs are less likely to accept receiving the COVID-19 vaccines compared with non-Arabs. Health authorities in these countries are advised to intensify their awareness-raising activities about the vaccines while ensuring fair distribution of them.